2020
DOI: 10.1002/adsc.201901324
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Perovskite as Heterogeneous Photocatalyst for Aminomethylation of Imidazo‐Fused Heterocycles

Abstract: A sustainable and cost-effective protocol for direct aminomethylation of imidazo-fused heterocycles by decarboxylative coupling reaction of N-phenylglycines with imidazo-fused heterocycles in the presence of CsPbBr 3 under the irradiation of visible light has been developed. This is the first example of CsPbBr 3 -catalyzed aminomethylation of imidazo-fused heterocycles. The eminent advantage of this work is in that, CsPbBr 3 is easily prepared and can be used at least 5 times without obvious reduction in its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…The control experiments using ammonium oxalate as the hole scavenger or K 2 S 2 O 8 as the electron scavenger gave the product 3 a in lower yields (9%-83% yields, entries 19-20, Table 1), which indicates that both hole and electron play essential roles in the process. [11] Accordingly, the optimal reaction conditions are established as shown in entry 11 (427 nm blue LEDs, g-C 3 N 4 0.75 mg/mL, K 2 CO 3 0.5 equiv., CH 2 Cl 2 , N 2 , rt, 16 h).…”
Section: Resultsmentioning
confidence: 99%
“…The control experiments using ammonium oxalate as the hole scavenger or K 2 S 2 O 8 as the electron scavenger gave the product 3 a in lower yields (9%-83% yields, entries 19-20, Table 1), which indicates that both hole and electron play essential roles in the process. [11] Accordingly, the optimal reaction conditions are established as shown in entry 11 (427 nm blue LEDs, g-C 3 N 4 0.75 mg/mL, K 2 CO 3 0.5 equiv., CH 2 Cl 2 , N 2 , rt, 16 h).…”
Section: Resultsmentioning
confidence: 99%
“…More decarboxylative coupling reactions under visible light irradiation have been illustrated. [101] Imidazole[1,2-a]pyridines are an importantm otif;t hey are widely present in natural compounds and bioactive molecules. The development of an efficient method to construct imidazole[1,2-a]pyridinesa nd their derivatives is of synthetic importance.A ss hown in Figure 12, as ustainable and cost-effective route for aminomethylation of imidazo-fused heterocycles via CsPbBr 3 -catalyzed decarboxylative coupling reactions under visible light Figure 10.…”
Section: Hybridhalide Perovskites For Photocatalytic Organic Synthesismentioning
confidence: 99%
“…Aminomethylation of imidazo-fused heterocycles catalyzedby perovskite via decarboxylative coupling. [101] Figure 13. Lead-free Cs 3 Bi 2 Br 9 perovskite-catalyzed ring-openingr eactiono f epoxides.…”
Section: Hybridhalide Perovskites For Photocatalytic Organic Synthesismentioning
confidence: 99%
“…Very recently, Shi et al . reported a sustainable approach for the aminomethylation of imidazo[1,2‐ a ]pyridines with N ‐arylglycines 46 through decarboxylative coupling using ScPbBr 3 as photo‐catalyst under visible light irradiation in DCE (Scheme ) . Various imidazo[1,2‐ a ]pyridines 1 and benzo[ d ]imidazo[2,1‐ b ]thiazole 2 and N ‐arylglycines 46 having a broad range of functional groups (EDGs and EWGs) reacted well and afforded the respective products 47 in 44–94% yields.…”
Section: C−c Bond Formationmentioning
confidence: 99%
“…Subsequently, intermediate A is transformed into α-amino radical intermediate B through proton transfer and decarboxylation in the presence of superoxide radical anion (O 2 *À ). Further oxidation of B by HO 2 * led to the formation of imine intermediate C. Finally, the electrophilic addition reaction of C on 1 produced the aminomethylated product 47.Very recently, Shi et al reported a sustainable approach for the aminomethylation of imidazo[1,2a]pyridines with N-arylglycines 46 through decarboxylative coupling using ScPbBr 3 as photo-catalyst under visible light irradiation in DCE (Scheme 30) [49]. Various imidazo[1,2-a]pyridines 1 and benzo[d]imidazo-[2,1-b]thiazole 2 and N-arylglycines 46 having a broad range of functional groups (EDGs and EWGs) reacted well and afforded the respective products 47 in 44-94% yields.…”
mentioning
confidence: 99%